2011
DOI: 10.1007/s00213-011-2271-y
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation between duration of action in the forced swim test in mice and nicotinic acetylcholine receptor occupancy with sazetidine, varenicline, and 5-I-A85380

Abstract: RATIONALE Nicotinic acetylcholine receptor (nAChR) agonists, partial agonists and antagonists have antidepressant-like effects in rodent models and reduce symptoms of depression in humans. OBJECTIVE The aim of this study was to determine if the β2* partial agonist sazetidine-A (sazetidine) showed an antidepressant-like effect in the forced swim test that was mediated by β2* nAChRs activation or desensitization. RESULTS Sazetidine, the less selective β2* partial agonist varenicline and the full β2* agonist … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
71
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(75 citation statements)
references
References 44 publications
3
71
1
Order By: Relevance
“…These studies indicated that during chronic infusion of saz-A for 2 weeks its steady-state concentration in brain was less than 10% of that in blood. Likewise, after 2 weeks of twice-daily injections of saz-A, its brain concentration 10 min after the last injection was also approximately only 10% that of blood, which agrees with a recent study that measured brain and blood concentrations of saz-A in mice after a single intraperitoneal injection (Caldarone et al, 2011). This is in marked contrast to both nicotine and varenicline, which were highly concentrated in brain during both methods of chronic administration; moreover, both the concentrations and the brain-to-blood ratios of nicotine and varenicline were similar to previously reported values (Ghosheh et al, 1999;Doura et al, 2008;Rollema et al, 2010).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…These studies indicated that during chronic infusion of saz-A for 2 weeks its steady-state concentration in brain was less than 10% of that in blood. Likewise, after 2 weeks of twice-daily injections of saz-A, its brain concentration 10 min after the last injection was also approximately only 10% that of blood, which agrees with a recent study that measured brain and blood concentrations of saz-A in mice after a single intraperitoneal injection (Caldarone et al, 2011). This is in marked contrast to both nicotine and varenicline, which were highly concentrated in brain during both methods of chronic administration; moreover, both the concentrations and the brain-to-blood ratios of nicotine and varenicline were similar to previously reported values (Ghosheh et al, 1999;Doura et al, 2008;Rollema et al, 2010).…”
Section: Discussionsupporting
confidence: 91%
“…3) and increase performance on tasks of attention . Furthermore, in preclinical tests these doses of saz-A produce behaviors that are consistent with potential antidepressant and/or antianxiety effects (Kozikowski et al, 2009;Turner et al, 2010Turner et al, , 2011Caldarone et al, 2011). Thus it seems that saz-A acts in the brain; yet even at doses two to six times these behaviorally active doses saz-A did not increase nAChR density.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Despite the far from ideal pharmacokinetic properties of 35, compounds with short half-lives are still able to display activity through the forced-swim test (FST) as a result of the short duration of the procedure (6 min). [28,29] While the pharmacokinetic profile of 35 would make it unsuitable for clinical development, and is by no means a viable lead candidate itself, we believe it is sufficient for proof-of-concept studies in the FST. To examine whether these compounds could penetrate the BBB, act on centrally expressed P2X 7 Rs and induce a behavioural response in vivo, the 3-pyridyl analogue 35 (highest LiPE value; Table 2) was tested in the FST.…”
Section: Resultsmentioning
confidence: 99%